2020
DOI: 10.1038/s41467-020-18538-x
|View full text |Cite
|
Sign up to set email alerts
|

Macrophage secretion of miR-106b-5p causes renin-dependent hypertension

Abstract: Myeloid cells are known mediators of hypertension, but their role in initiating renin-induced hypertension has not been studied. Vitamin D deficiency causes pro-inflammatory macrophage infiltration in metabolic tissues and is linked to renin-mediated hypertension. We tested the hypothesis that impaired vitamin D signaling in macrophages causes hypertension using conditional knockout of the myeloid vitamin D receptor in mice (KODMAC). These mice develop renin-dependent hypertension due to macrophage infiltratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
32
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(40 citation statements)
references
References 57 publications
3
32
0
Order By: Relevance
“…Moreover, vitamin D has been shown to induce angiotensin-converting enzyme 2 expression, the enzyme that cleaves angiotensin II to angiotensin 1–7, further counteracting the excess of angiotensin II and, hence, promoting the anti-fibrotic, anti-inflammatory, and anti-hypertensive functions of angiotensin 1–7 [ 19 , 20 ]. Lastly, immune cells that lack VDR have been reported to directly impact on the secretion of miR-106b-5p, which, in turn, may increase renin production by acting on juxtaglomerular cells, thus suggesting the role of inflammation as the cause of renin-driven hypertension [ 21 ].…”
Section: Vitamin D and The Cardiovascular Systemmentioning
confidence: 99%
“…Moreover, vitamin D has been shown to induce angiotensin-converting enzyme 2 expression, the enzyme that cleaves angiotensin II to angiotensin 1–7, further counteracting the excess of angiotensin II and, hence, promoting the anti-fibrotic, anti-inflammatory, and anti-hypertensive functions of angiotensin 1–7 [ 19 , 20 ]. Lastly, immune cells that lack VDR have been reported to directly impact on the secretion of miR-106b-5p, which, in turn, may increase renin production by acting on juxtaglomerular cells, thus suggesting the role of inflammation as the cause of renin-driven hypertension [ 21 ].…”
Section: Vitamin D and The Cardiovascular Systemmentioning
confidence: 99%
“…In the blood vessels, vitamin D may modulate vascular tone via regulation of calcium influx and stimulation of nitric oxide production in smooth muscle cells ( 38 , 39 ). In addition, it also exhibits anti-inflammatory actions, inhibition of foam cell formation, and reduction of thrombogenicity and vascular calcifications ( 39 , 40 ). Vitamin D deficiency accelerates CAD progression by increasing karyopherin α4 and nuclear factor kappa beta levels ( 41 ).…”
Section: Discussionmentioning
confidence: 99%
“…Given that inflammation is a common factor in vascular pathologies, considerable research linking ncRNAs to the inflammatory responses involved in hypertension has been established [60][61][62]. Consistent with this idea, several studies have identified hypertension-related miRNAs such as miR-106b-5p, microRNA-124, and miR-129, which possibly influence hypertension by modulating inflammation [63][64][65][66][67]. Based on the high relevance and association of IL-1β to hypertension, recent studies have led to the discovery of several ncRNAs that target this gene.…”
Section: Regulation Of Il-1β By Ncrnasmentioning
confidence: 91%